2013
DOI: 10.1680/macr.12.00013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observations on reinforced concrete bearing walls subjected to all-sided fire exposure

Abstract: Experimental observations were made on eight reinforced concrete wall specimens, with all sides being exposed to an International Organization for Standardization standard heating curve. The main variables were wall thickness, level of axial load, reinforcement ratio, concrete compressive strength and curing period. During the test, temperature increases in the wall, and the heating time plotted against axial deformations, were measured. The effects of the main variables on the fire resistance and axial deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In recent studies by Lee et al [21] and Ryu et al [14], the performance of reinforced concrete walls subjected to two-sided ISO 834 standard fire was investigated. Lee et al [21] and Ryu et al [14] exposed the test specimens simultaneously from two sides using a horizontal furnace and two-zone heating chamber as shown in Figure 2.4. Lee et al [21] conducted tests for a total of eight reinforced concrete walls which were 1.1 to 1.2 metres wide and 1.75 metres high.…”
Section: Previous Experimental Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies by Lee et al [21] and Ryu et al [14], the performance of reinforced concrete walls subjected to two-sided ISO 834 standard fire was investigated. Lee et al [21] and Ryu et al [14] exposed the test specimens simultaneously from two sides using a horizontal furnace and two-zone heating chamber as shown in Figure 2.4. Lee et al [21] conducted tests for a total of eight reinforced concrete walls which were 1.1 to 1.2 metres wide and 1.75 metres high.…”
Section: Previous Experimental Studiesmentioning
confidence: 99%
“…Lee et al [21] and Ryu et al [14] exposed the test specimens simultaneously from two sides using a horizontal furnace and two-zone heating chamber as shown in Figure 2.4. Lee et al [21] conducted tests for a total of eight reinforced concrete walls which were 1.1 to 1.2 metres wide and 1.75 metres high. As shown in Figure 2.4(a), the specimens were first placed on a reinforced concrete platform located in the horizontal fire furnace which was generally used for evaluating the fire resistance of horizontal construction elements.…”
Section: Previous Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Results identified several parameters influencing the fire resistance of walls. These parameters included height-to-thickness ratio, concrete strength, reinforcement cover, eccentric load (Crozier and Sanjayan, 2000), polypropylene fibers (Tuan et al, 2013; Xiao et al, 2004), aggregate size (Ahmad et al, 2011), aggregate type (Go et al, 2012), fire exposure on all sides (Lee et al, 2013), and boundary conditions (Mueller and Kurama, 2015). Very few fire tests have been found for C-PSW/CF (Wei et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the experiments conducted by Crozier and Sanjayan [1], 18 concrete walls with different height-to-thickness ratios, reinforcement covers, concrete strengths, and varying levels of eccentric load were tested to figure out the influence of these variables on the performance of concrete walls exposed to a fire on one side. Lee and Lee [2], and Lee et al [3] tested another 8 concrete walls subjected to the fire exposure on all sides with different thicknesses, axial loads, and concrete compressive strengths. Results indicated that code predictions on the fire resistance for the walls are either overestimated or underestimated and need further experimental verification.…”
Section: Introductionmentioning
confidence: 99%